Describing natural colors with Munsell and NCS color systems - Pastilha, Ruben Carpinteiro (2019)
The Munsell Color System and the Natural Color System are widely used but they have some limitations due to the manufacturing process and sampling choices. To estimate quantitatively these limitations we compared the colors of natural scenes with the colors represented by these systems under a wide range of illuminants. Spectral data from the two systems and from natural scenes were used in the analysis. It was found that a considerable portion of natural colors are not accounted by these systems, mainly colors with low lightness levels. Under D65 the Munsell Color System color volume corresponds to 72% of the Natural Color System color volume which in turn represents only 53% of the natural scenes color volume. If individual colors are considered, less than half are contained within these systems. To obtain a complete match to the natural colors contained by the color systems thresholds of 7 and 5 CIELAB units would be required for Munsell Color System and Natural Color System, respectively. Variations with the illuminant are generally modest showing that both system work similarly across different illuminations. Although these Color Systems have limitations in describing low lightness colors they perform quite well for medium to high levels of lightness.